2019
DOI: 10.7567/1347-4065/ab2dab
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-ray irradiation-induced mobility enhancement of 4H-SiC NMOSFETs with a Ba-silicate interface layer

Abstract: 4H-SiC n-channel metal oxide semiconductor field effect transistors (NMOSFETs) with a Ba-silicate interface layer were irradiated with gamma-rays up to 850 kGy at room temperature. Above 600 kGy, the field effect mobility increased from 12 to 18 cm2 V−1 s−1. The narrower channel in the NMOSFETs enhanced radiation responses, such as mobility enhancement and threshold voltage shift. These results indicate that the edge of the channel significantly modifies the electrical characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…20) Unlike other elements, it has been reported that Ba, an alkaline earth element, does not behave as a mobile ion because of its large ion size. 12,21) In previous reports, Ba of a few monolayers or less was deposited onto SiC substrates beneath cap SiO 2 dielectrics, followed by oxidation annealing. Fujita et al demonstrated that metal-enhanced oxidation (MEO) occurs during annealing at above 850 °C in the presence of Ba.…”
Section: Introductionmentioning
confidence: 99%
“…20) Unlike other elements, it has been reported that Ba, an alkaline earth element, does not behave as a mobile ion because of its large ion size. 12,21) In previous reports, Ba of a few monolayers or less was deposited onto SiC substrates beneath cap SiO 2 dielectrics, followed by oxidation annealing. Fujita et al demonstrated that metal-enhanced oxidation (MEO) occurs during annealing at above 850 °C in the presence of Ba.…”
Section: Introductionmentioning
confidence: 99%
“…We have already demonstrated total ionizing dose effect (TID) resistance of 4H-SiC MOSFETs and some reports also showed that the MOSFETs work even after high irradiation doses exceeding 100 Mrad [12][13][14]. The thick embedded oxide film makes SOI devices relatively vulnerable to TID, however, we suggest that TID effects can be reduced by thinning the BOX layer to the same thickness as the gate oxide film.…”
Section: Introductionmentioning
confidence: 71%
“…These properties mean SiC crystal has a hardness to radiation and has potential for electronic devices with low soft errors. Operation of 4H-SiC bipolar junction transistors (BJTs), junction field effect transistors (JFETs), and metal-oxide-semiconductor transistors (MOSFETs) have been demonstrated in high temperature environments [4][5][6][7][8][9][10][11][12][13][14]. In terms of the image sensor, 4H-SiC has already demonstrated operation as a UV imaging system with 256 pixels at 400°C [15].…”
Section: Introductionmentioning
confidence: 99%